Incremental Dynamic Analysis of Horizontal Pressure Vessels with Their Piping Systems - Mahdi Sharifi; Zeinab Maleki; Bijan Sayyafzadeh (پژوهش‌های زیرساخت‌های عمرانی, 2023)
Reduction and management of risk of industrial plant especially energy is an important concern. Probabilistic and reliability method are used in risk and cost estimations. Oil, Gas and Petrochemical plant are the most energy producer plants that are in focus of cost, life and operation. These plants consist of several units, parts and equipment’s. In order to study the risk of plants, it is needed to study the equipment’s. The main goal of this research is probabilistic seismic assessment of fixed horizontal vessels. In this paper, finite element model of designed and constructed vessels in a real project is prepared and incremental dynamic analysis (IDA) is performed. Response of vessels components including the vessel body stress, piping stress, flange and elbow deformations, anchor bolt stress are extracted and their related limit state are defined. Finally the fragility curve of vessels components is prepared. The result shows that flange connection is the components that are potential for starting the damage of vessels.